Rancang Bangun Sistem Informasi Kampus Berbasis Website dengan Integrasi Backup Database Otomatis ke Cloud - Nisrina Difa Lediana; Najwa Ainur Rokhmah; Elsha Sofira (Journal of Science, Technology, and Innovation, 2025)
This study aims to design and implement a web-based campus information system integrated with an automatic cloud-based database backup mechanism to improve data security and operational efficiency. The research adopts a system development approach through needs analysis, system design using UML, interface prototyping with Figma, and implementation using PHP, MySQL, and cloud storage integration. The backup mechanism is automated using scheduled processes to ensure consistent data protection without manual intervention. System evaluation was conducted through a questionnaire distributed to 50 respondents, selected using the Slovin formula, to measure user perceptions of efficiency, reliability, and system performance. The results indicate a high level of user acceptance, with an overall average score of 4.44, reflecting strong system reliability and effectiveness. The automatic backup integration significantly reduces the risk of data loss, enhances accessibility, and optimizes cloud storage utilization. The findings demonstrate that the developed system provides a robust solution for campus data management and supports sustainable digital transformation in higher education institutions.